2016
DOI: 10.1038/gim.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in JMJD1C are involved in Rett syndrome and intellectual disability

Abstract: Purpose:Autism spectrum disorders are associated with defects in social response and communication that often occur in the context of intellectual disability. Rett syndrome is one example in which epilepsy, motor impairment, and motor disturbance may co-occur. Mutations in histone demethylases are known to occur in several of these syndromes. Herein, we aimed to identify whether mutations in the candidate histone demethylase JMJD1C (jumonji domain containing 1C) are implicated in these disorders.Genet Med 18 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Jmjd1c encodes a putative histone demethylase. Sáez et al reported heterozygous de novo variants in JMJD1C in 2 unrelated individuals with Rett syndrome and showed reduced dendritic complexity with small interfering RNA knockdown in mouse hippocampal neurons. C57BL/6J codes for a leucine at position 1715, whereas C57BL/6NJ and other strains have a proline in this position (rs13480628), although the effect on protein function is predicted to be benign .…”
Section: Discussionmentioning
confidence: 99%
“…Jmjd1c encodes a putative histone demethylase. Sáez et al reported heterozygous de novo variants in JMJD1C in 2 unrelated individuals with Rett syndrome and showed reduced dendritic complexity with small interfering RNA knockdown in mouse hippocampal neurons. C57BL/6J codes for a leucine at position 1715, whereas C57BL/6NJ and other strains have a proline in this position (rs13480628), although the effect on protein function is predicted to be benign .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, germline variants in the H3K9 demethylase JMJD1C (MIM: 604503), which is a gene that shows large regions of homology with KDM3B, are found in individuals with intracranial germ cell tumors and with NDDs. 26,27 Rare de novo KDM3B variants (c.4216C>T [p.Arg1406Trp] 28 and c.2624del [p.Leu875Argfs*8]) 4 have been reported in two individuals with schizophrenia and ID, respectively. However, the associated phenotypes have not been fully reported, nor was the causality of these variants confirmed.…”
mentioning
confidence: 99%
“…The p.F2115C mutation is in the JmjC domain, a domain family that is part of the cupin metalloenzyme superfamily. Mutations in this gene are associated with Rett syndrome and intellectual disability (Saez et al, ). TCF12 encodes a member of the basic helix‐loop‐helix E‐protein family that recognizes the consensus‐binding site (E‐box) CANNTG.…”
Section: Discussionmentioning
confidence: 99%